(untitled) (L’uomo nero. Materiali per una storia delle arti della modernità, 2022)
Ambienti per design un suono udito una cosa vista (EXIT) was published by Zeno Birolli in 1983, within the book Sorbi, tordi & nitidezze, that included old and new essays under the subtitle Arte in Italia dopo la Metafisica. The book – pretty known – was the result of a strong season of studies and projects: Birolli planned to propose a kind of anthology of a decade of studies on art of interwar period. Among the new essays published in the book, Ambienti per design was one of most influential text since both number of pages and subjects. The text is the detailed description of interiors for exhibitions dedicated to house and modern furniture held at VI Triennale in 1936; however, the prevalent topic is based on the idea of “a connection between earlier Metaphysics by De Chirico and some painters and sculptors of post-metaphysics tendency, and architectonic rationalism (‘30s and ‘40s), as well as the scenic space by Antonioni”.